Evaluation of the impact of lean tools on safety performance in Malaysia’s manufacturing firms - Wang, Li Khang (2023)
Occupational health and safety considerations are key aspects of manufacturing firms, along with profitability. Implementing lean tools is a comprehensive method for continuously improving industrial processes. The primary focus of the study is to evaluate how lean tools affect Malaysia’s manufacturing firms’ safety performance. The objective of this study is to develop the conceptual framework of lean tools and safety performance and to examine the hypotheses and the relationship between lean tools and safety performance. The variables to be examined in this study are continuous flow (CF), total preventive maintenance (TPM), employee involvement (EI), and safety performance (SP). Despite the increasing adoption of lean principles and practises to improve operational efficiency, there remains a significant knowledge gap regarding their influence on safety performance. Furthermore, manufacturing companies may lack awareness of the specific lean tools that should be prioritised to enhance safety performance. This lack of knowledge can lead to the inefficient allocation of time and resources, hindering their ability to effectively improve safety outcomes. A total of 134 responses of questionnaires were collected from all of the manufacturing companies listed on the Federation of Malaysian Manufacturers (FMM) and Wesley Malaysia websites. The data is analysed using the PLS-SEM analytical method with SmartPLS 4 software. The findings of this study indicate that continuous flow, total preventive maintenance, and employee involvement all significantly improve safety performance. Employee involvement has the greatest impact on safety performance, with a beta coefficient of 0.304. Followed by continuous flow and total preventive maintenance with beta coefficients of 0.274 and 0.232, respectively. Moreover, Importance-performance Map Analysis (IPMA) indicates that EI is the most pertinent construct for managerial action. In addition, it suggests Malaysia’s manufacturing firms keep up their performance on CF. On the other hand, the industries may choose to maintain their existing performance on TPM or refocus on other constructs with high importance and performance. In conclusion, the findings of this study will contribute to filling the knowledge gap in the Malaysian context, providing evidence-based recommendations and guidance for Malaysia’s manufacturing firms.